2016
DOI: 10.1007/978-3-319-44156-6_31
|View full text |Cite
|
Sign up to set email alerts
|

Control-Based Design of a Five-Bar Mechanism

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The intersection points of j i (j = 1, 2) and the image plane boundary are denoted as P 1 ij , P 2 ij . Similarly as it was done in [8], we add a random shift in pixels on P 1 ij , P 2 ij (Fig. 4) to model the noise we got from the observation.…”
Section: Positioning Error Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intersection points of j i (j = 1, 2) and the image plane boundary are denoted as P 1 ij , P 2 ij . Similarly as it was done in [8], we add a random shift in pixels on P 1 ij , P 2 ij (Fig. 4) to model the noise we got from the observation.…”
Section: Positioning Error Modelsmentioning
confidence: 99%
“…In this work, the accuracy performance of leg-based visual servoing and image moment visual servoing will be taken into account in the robot design process, so that we can get a DELTA robot for a given controller with the best accuracy performance. Compared to the previous work [8], this is the first time that control-based design approaches are applied to the optimal design of a spatial robot. Also this is the first time that image moment visual servoing is taken into account as one of the controllers in control-based design.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason we decided to define a controller based on the observation of the distal links, as in Andreff et al (2007). However, as shown in Briot et al (2015) this controller is not free of singularities, that effect its accuracy performance which that not only depend on the camera localisation and specifications but also on the robot dimensions as shown in Kaci et al (2016). Thus the optimization process must take all this parameters into account.…”
Section: Design Processmentioning
confidence: 99%
“…• In order to ensure the robot accuracy even with the variability in the wooden link dimensions, sensor-based controllers could be used [10]. However, as shown in [11], positioning accuracy of sensor-based controllers (obviously) depends of the number and types of sensors that are used for the robot control, but also, in certain cases, of the robot geometric parameters [12]. Therefore, the robot design process must take into account performance criteria coming from usual physical properties [13] but also from the type of controller that will be implemented on the robot.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that expressions (10) and (11) are approximated functions obtained thanks to a Taylor series expansion at the order two of the expression of the robot end-effector deformation u e with respect to the components of the vector π E [14]. We tested their validity and our results shown that, for the mechanical parameters of the acetylated beech, the error of approximation is lower than 10 %.…”
mentioning
confidence: 97%